Time Machine Fashion: Neo-Victorian Style in Twenty-First Century Subcultures - Feldman-Barrett, Christine (Australasian Journal of Victorian Studies, 2013)
For the last several decades, there has been a pronounced influence of “retro” fashion and style on various youth subcultures. This occurrence has been in the form of larger, cultural trends in both the underground and mainstream, such as the Teddy Boy and Mod revivals of the late seventies. However, until recently, it has been far less common for youths to identify stylistically with a more distant past. Alongside a more longstanding fascination among goths with Stoker-era vampire chic, contemporary steampunks and Lolitas also adopt many signs and symbols of Victoriana. While steampunks romanticise mid-nineteenth century technology, both real and imagined, Lolitas, an originally Japanese subculture, are fascinated with a nineteenth century unrelated to their own nation’s history. This article examines the lineage of so-called neo-Victorian subcultures, how they compare to one another, and what symbolic value they hold for young people today.